Rapid and quantitative detection of urinary Cyfra21-1 using fluorescent nanosphere-based immunochromatographic test strip for diagnosis and prognostic monitoring of bladder cancer - Qifang Lei; Linlin Zhao; Shuixian Ye; Yue Sun; Fangjie Xie; Hong Zhang; Fangjian Zhou; Song Wu (Artificial Cells, Nanomedicine, and Biotechnology, 2019)
Bladder cancer is a common malignant tumour with high recurrence rate. Cytokeratin 19 fragments (Cyfra21-1) in urine has been regarded as a promising biomarker for the prognosis and diagnosis of bladder cancer due to the relevance of its high urinary level to the bladder cancer patients. However, currently detection methods of Cyfra21-1 have their limits, such as complicated steps, limited sensitivity or unsatisfying specificity. In this study, we developed a novel time-resolved fluoroimmuno test strip by using europium chelate microparticle (Eu-CM). Detection was performed in simple steps by carrying drops of sample into the well of the test strip, waiting for 15 min and inserting the strip into a fluorescence strip reader for quantitation. The standard curve equation of the test strip was y = 0.0177x + 0.01 (R2 = .9993). In the analysis of human urine samples (n = 115), it demonstrated a good performance (accuracy: CV < 10%, AUC: 0.989). With the cut-off value of 81 ng/mL, the sensitivity and specificity for bladder cancer were 92.86 and 100%, respectively. In comparison to ELISA and electrochemiluminescence methods, the Eu-CM based time-resolved fluoroimmuno test strip provided a rapid, sensitive and reliable method for monitoring bladder cancer. It may be applied as a non-invasive approach for in point-of-care for bladder cancer detection.